2019
DOI: 10.5114/wiitm.2019.86774
|View full text |Cite
|
Sign up to set email alerts
|

Guiding role of seminal tract anatomical study in transurethral seminal vesiculoscopy.

Abstract: Introduction: There have been problems with low qualification operator-related complications and failures of transurethral seminal vesiculoscopy (TSV) in China. Aim: To study the guiding role of seminal tract anatomical study (STAS) in TSV. Material and methods: We performed STAS to study the structure, morphology, duct trajectory, and anatomical relationships between the seminal vesicles and the adjacent tissue in pelvic specimens from 12 adult cadavers. Then the surgical effects and complications of 82 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In this study, we implemented the preoperative ultrasound-guided seminal vesicle radiography technique combined with CT three-dimensional reconstruction and found the path of the ejaculation tubes in some cases. We found that the path was consistent with that in a previous study of cadaver specimens (Pang et al, 2020). We randomly divided 32 EDO or haemospermia patients who were scheduled to undergo TSV surgery into two groups, namely, with or without implementation of preoperative ultrasound-guided seminal vesicle radiography combined with the CT three-dimensional reconstruction technique.…”
Section: Ta B L E 3 Surgical Parameterssupporting
confidence: 66%
See 4 more Smart Citations
“…In this study, we implemented the preoperative ultrasound-guided seminal vesicle radiography technique combined with CT three-dimensional reconstruction and found the path of the ejaculation tubes in some cases. We found that the path was consistent with that in a previous study of cadaver specimens (Pang et al, 2020). We randomly divided 32 EDO or haemospermia patients who were scheduled to undergo TSV surgery into two groups, namely, with or without implementation of preoperative ultrasound-guided seminal vesicle radiography combined with the CT three-dimensional reconstruction technique.…”
Section: Ta B L E 3 Surgical Parameterssupporting
confidence: 66%
“…This problem leads to higher surgical failures than the studies have reported. The percentage of cases in which seminal vesiculoscopy of the seminal vesicle failed was approximately 13%-46%, which was much higher than the success rate reported in recent articles (Christodoulidou, Parnham, & Nigam, 2017;Liao et al, 2019;Miao et al, 2019;Pang et al, 2020;Zhang et al, 2017).…”
Section: Ta B L E 3 Surgical Parametersmentioning
confidence: 59%
See 3 more Smart Citations